2021
DOI: 10.1111/mmi.14733
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene resistance in Trypanosoma congolense is not caused by reduced transport capacity but associated with reduced mitochondrial membrane potential

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 123 publications
2
40
0
Order By: Relevance
“…It has been widely reported that in brucei group trypanosomes drug sensitivity and resistance is often linked to the presence or absence of particular transport proteins, such as TbAT1, TbAQP2, TbMFST and TbAAT6, which mediate the uptake of diamidines and melaminophenyl arsenicals (TbAT1 and TbAQP2), suramin (TbMFST) and eflornithine (TbAAT6), respectively [ 26 , 29 , 41 ]. However, the now well-established models of drug transport and resistance do not seem to apply to all African trypanosome species, as recently shown for diminazene uptake and resistance in T. congolense [ 42 ]. We here investigate whether the relatively low sensitivity of T. congolense for diamidines, melaminophenyl arsenicals and suramin is linked to the absence of orthologues of TbAT1, TbAQP2 and TbMFST.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that in brucei group trypanosomes drug sensitivity and resistance is often linked to the presence or absence of particular transport proteins, such as TbAT1, TbAQP2, TbMFST and TbAAT6, which mediate the uptake of diamidines and melaminophenyl arsenicals (TbAT1 and TbAQP2), suramin (TbMFST) and eflornithine (TbAAT6), respectively [ 26 , 29 , 41 ]. However, the now well-established models of drug transport and resistance do not seem to apply to all African trypanosome species, as recently shown for diminazene uptake and resistance in T. congolense [ 42 ]. We here investigate whether the relatively low sensitivity of T. congolense for diamidines, melaminophenyl arsenicals and suramin is linked to the absence of orthologues of TbAT1, TbAQP2 and TbMFST.…”
Section: Resultsmentioning
confidence: 99%
“…In much of sub-Saharan Africa, trypanosomiasis in (domesticated) animals is caused primarily by infection with T. congolense ; the condition is treated predominantly with diminazene aceturate but resistance to this drug is widespread [ 11 ]. Both the primary fractions of PNG propolis and the isolated compounds were tested on a standard drug-sensitive strain of T. congolense , IL3000, and the derived diminazene-resistant cell line 6C3 [ 29 ]. The crude extract displayed promising activity against T. congolense ( Table 6 and Table 7 ), including the resistant line, very close to the value obtained against T. b. brucei ( Table 3 ), but none of the individual fractions matched this.…”
Section: Resultsmentioning
confidence: 99%
“…There remain many triterpenoids to be isolated from the PNG propolis sample and there may be more active compounds present in the mixture given that its activity was higher than most of the isolated compounds. Importantly, 20-hydroxybetulin was significantly (>2-fold) active against drug-resistant strains of T. b. brucei and T. congolense , despite the drug resistance mechanisms being very different in the two species [ 29 , 30 ]. Overall, it would seem that 20-hydroxybetulin, which displayed low toxicity against mammalian cell lines, could be a promising lead compound to systematically explore the SAR against African drug-resistant trypanosomiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current methods of disease control centre around chemotherapy and prophylaxis (reviewed in [3]), but the very few available veterinary trypanocidal drugs have been used extensively for decades, resulting in resistance and inadequate protection [5][6][7][8]. In contrast to T. brucei [9], the resistance mechanisms of T. congolense are still poorly understood [10]. As such, there is a critical need for the development of new and improved chemotherapeutics to manage AAT [3,11], and furthering our knowledge of how T. congolense develops resistance to drugs can facilitate optimising the lifetime of both existing and new drugs.…”
Section: Introductionmentioning
confidence: 99%